Rare Presentation of Metastatic Cystic Trophoblastic Tumor in a Patient Without Prior Chemotherapy - Michael L. Wang; Jonathan B. McHugh; Alon Z. Weizer; Todd M. Morgan; Arul M. Chinnaiyan; Andrew P. Sciallis; Amir Lagstein; Daniel E. Spratt; Rohit Mehra (Urology Case Reports, 2017)
Cystic trophoblastic tumor (CTT) is a rare testicular germ cell tumor (GCT) predominantly seen in post-chemotherapy patients. It is prognostically similar to teratoma and requires no additional chemotherapy in the absence of a nonteratomatous GCT component. We report a case of metastatic CTT in a patient with primary testicular teratoma without prior chemotherapy. Retroperitoneal lymph node metastases contained teratoma, embryonal carcinoma, and CTT. The CTT was β-hCG positive and SALL4 negative by immunohistochemistry (IHC). CTT can arise in metastatic testicular GCT in treatment naïve patients. An important differential diagnosis is choriocarcinoma due to treatment implications, and SALL4 IHC may help.